Assessment of the Appropriateness of Ceftazidime Use in a Tertiary Teaching Hospital, Northern Ethiopia - Gebremichael TG; Gebreyesus HH; Gebremariam A (Drug, Healthcare and Patient Safety, 2019)
Teklu Gebrehiwot Gebremichael,1 Hiluf Hindeya Gebreyesus,2 Alem Gebremariam1 1Clinical Pharmacy Unit, School of Pharmacy, College of Health Sciences, Mekelle University, Mekelle, Tigray, Ethiopia; 2Medical Physiology Unit, Biomedical Division, School of Medicine, College of Health Sciences, Mekelle University, Mekelle, Tigray, EthiopiaCorrespondence: Teklu Gebrehiwot GebremichaelClinical Pharmacy Unit, School of Pharmacy, College of Health Sciences, Mekelle University, Mekelle, Tigray, EthiopiaTel +251-933-730-004Fax +251-34-416-681Email tekluu2020@gmail.comBackground: Ceftazidime is nowadays one of the most commonly used antibiotics due to its high antibacterial potency, wide spectrum of activity, and low potential for toxicity. However, the global trend shows huge misuse of ceftazidime.Objective: This study was conducted to assess the appropriateness of ceftazidime use and to identify areas of intervention to prevent inappropriate use in different wards of Ayder Compressive Specialized Hospital, a tertiary teaching Hospital, Mekelle-Ethiopia.Methods: A facility-based prospective cross-sectional study design was steered on 327 patients who received ceftazidime during their hospitalization in the selected wards from February 1 to April 30, 2019.Results: In the assessment of the appropriateness of ceftazidime use, 2,084 (70.8%) were appropriate. Appropriateness of indication was 295 (90.2%), the effectiveness of ceftazidime use was 221 (67.6%), correct dose of ceftazidime use was 264 (80.4%), and the correct frequency of ceftazidime use was 230 (70.3%). Its use was empiric in 275 participants (84.1%) and specific in 52 (15.9%) participants. The most common indication for ceftazidime use was uncomplicated pneumonia, at 112 (34.3%). One hundred and seventy-one (52.3%) participants had intervention to prevent inappropriate use of ceftazidime. Changing the drug combination (96, 29.4%), increasing the dose (13, 4%), decreasing the dose (21, 6.4%), holding the (21, 6.4%), and discontinuation of ceftazidime (20, 6.1%) were among the interventions.Conclusion: This study revealed that more than one-fourth of the ceftazidime use was inappropriate. This may lead to the emergence of resistant pathogens which in turn lead to treatment failure and increased the cost of therapy. Therefore, adherence to current evidence-based guidelines and initiating antimicrobial stewardship are recommended.Keywords: ceftazidime, drug use evaluation, appropriateness, resistance